Update and validation of the Canadian Behavior, Attitude and Nutrition Knowledge Survey (C-BANKS 2.0) - Lafave, Lynne M. Z.; Hayek, Joyce; Lafave, Mark R. (Frontiers in Public Health, 2023)
Aim Understanding knowledge, attitudes and behaviors related to nutrition is crucial in developing effective intervention strategies to promote healthy eating habits. This study revised and updated the Canadian Behavior, Attitude and Nutrition Knowledge Survey (C-BANKS) to align with the current Canada’s Food Guide and dietary guidance and report on its reliability and validity with a new population. Method Data from 167 early childhood educators were recruited to test the revised C-BANKS’ reliability and validity. Reliability, as measured by internal consistency, was assessed using Cronbach’s alpha, while concurrent validity was determined by correlating the C-BANKS 2.0 scores with the CHEERS (Creating Healthy Eating and Active Environments Survey) and Mindful Eating Questionnaire (MEQ). Responsiveness was assessed by comparing a baseline C-BANKS 2.0 score to a post-test score after completing an online healthy eating and physical activity educational intervention. Results The adapted C-BANKS 2.0 questionnaire demonstrated good internal consistency (Cronbach’s alpha >0.70) and construct validity with related measures CHEERS and MEQ (p < 0.05). The C-BANKS 2.0 demonstrated strong responsiveness. Specifically, C-BANKS 2.0 scores increased after the nutrition education intervention (p < 0.001). Additionally, there were no signs of floor or ceiling effects. Conclusion The adapted C-BANKS 2.0 demonstrated satisfactory internal consistency, construct validity, and responsiveness to measure of nutrition knowledge, attitudes, and behaviors in an early childhood educator population. The revised C-BANKS 2.0 provides insight into the key factors that influence dietary habits thereby informing the design and evaluation of effective nutrition community intervention programs.